Vidas supérfluas: a invenção da pressa - Guisard, Luís Augusto De Mola (2016)
The thesis aimed at understanding how hurriedness originated as a symbol of contemporary city life, and seeking possibilities of resisting such hegemony. The research was driven by an individual feeling of uneasiness about hurriedness as a universal value: hurriedness deviated from its natural role in order to meet life-specific urgencies, such as the urgency of an escaping animal, a child going for a moment of fun, or a bodyguard to the rescue. Hurriedness is constant in city life, which does not seem consistent with man’s vital impulses. It is an outer element that arose at some point in history. Taking as hypothesis that the hurriedness we currently experience, disconnected from our nature, denies life values, this paper consisted in a genealogical study of hurriedness. Such genealogical analysis was permeated by the idea that an extemporary posture, of non-compliance to the current values is required, as a way of enabling criticism to the hurriedness value. In order to serve this purpose, two main authors were used as reference: Nietzsche and Foucault. The first provided the cornerstone to face the task of attempting to understand hurriedness in its actual dimensions, while the latter enabled outlining the elements of the historical construction of hurriedness, including in the most recent period: throughout the twentieth century. As a resource of analysis, the figure used was that of a motorcycle courier, which a hasty professional in the São Paulo metropolis, representing the metaphor of a superfluous life, a hostage of productive hurriedness that serves the urgency of capital, not of life. Indeed, the motorcycle courier is the metaphor of the hastiness that is often true to all of us. The analysis enabled reaching the idea that hurriedness was a historical construction. It meets the contemporary rationality, since its early origins when the intelligible world was valued over the sensitive world of the Socratic and Platonic traditions, making its way to the neoliberal order of the twentieth century, by formatting the self-made man-machine, wrapped in a spirit of gravity. The conclusion is all the more exciting: there has been a form of society when constant hurriedness was not prevalent, during the tragic period, and currently, there are signs of resistance to hurriedness, such as those represented by the movements asserting the logic of slow. After all, according to Nietzsche’s Zarathustra, “Not by wrath does one kill, but by with laughter. Come, let us kill the spirit of gravity!”